Positive impact of the Portuguese smoking law on respiratory health of restaurant workers - Madureira, Joana (2013)
The impact of smoke-free law on the respiratory and sensory symptoms among restaurant workers was evaluated. Fifty-two workers in 10 Portuguese restaurants were interviewed before and 2 years after implementation of the smoke-free law. A significant reduction in self-reported workplace environmental tobacco smoke (ETS) exposure was observed after the enforcement of the law, as well as a marked reduction in adverse respiratory and sensory symptoms such as dry, itching, irritated, or watery eyes, nasal problems, and sore or dry throat or cough, between pre- and post-ban. This study demonstrates that the smoking ban was effective in diminishing the exposure symptoms among workers and consequently in improving their respiratory health. These observations may have implications for policymakers and legislators in other countries currently considering the nature and extent of their smoke-free workplace legislation.